Highly diverse recombining populations of Vibrio cholerae and Vibrio parahaemolyticus in French Mediterranean coastal lagoons - Esteves, Kevin; Mosser, Thomas; Aujoulat, Fabien; HERVIO-HEATH, Dominique; MONFORT, Patrick; Jumas-Bilak, Estelle (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus and Vibrio cholerae are ubiquitous to estuarine and marine environments. These two species can induce infections in humans. Therefore understanding the structure and dynamics of non-pandemic environmental populations in temperate regions, such as Mediterranean coastal systems, is important if we are to evaluate the risks of infection to humans. Environmental isolates of V. cholerae (n=109) and V. parahaemolyticus (n=89) sampled at different dates, stations and water salinities were investigated for virulence genes and by a multilocus sequence-based analysis (MLSA). V. cholerae isolates were all ctxA negative and only one isolate of V. parahaemolyticus displayed trh2 gene. Most Sequence Types (ST) corresponded to unique ST isolated at one date or one station. Frequent recombination events were detected among different pathogenic species, V. parahaemolyticus, V. cholerae, Vibrio mimicus and Vibrio metoecus. Recombination had a major impact on the diversification of lineages. The genetic diversity assessed by the number of ST/strain was higher in low salinity conditions for V. parahaemolyticus and V. cholerae whereas the frequency of recombination events in V. cholerae was lower in low salinity. Mediterranean coastal lagoon systems housed V. cholerae and V. parahaemolyticus with genetic diversities equivalent to the worldwide diversity described so far. The presence of STs found in human infections as well as the frequency of recombination events in environmental vibrios populations could predict a potential epidemiological risk.